2022
DOI: 10.7600/jpfsm.11.79
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological study of amateur soccer players: a 17-month study to determine injury and pain

Abstract: Injury can possibly change an athlete's career. To date, few epidemiological studies have been made of amateur soccer players. More data is needed to allow medical professionals to develop realistic injury prevention and conditioning programs for the amateur level. The purpose of this study was to determine injury incidence, common injury types and body regions, and pain in amateur soccer players. Soccer-related injury and pain data were collected daily in June 2016 thorough October 2017 involving 76 amateur s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
1
1
0
Order By: Relevance
“…This is in line with previous studies on amateur players [6,8,13]. Even though some studies reported a greater percentage of ankle sprains [10] or joint/ligamentous injuries in total [6,7] than the present study, it is clear that injury prevention strategies which aim to reduce muscle and ligamentous injuries may be particularly beneficial for amateur players.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is in line with previous studies on amateur players [6,8,13]. Even though some studies reported a greater percentage of ankle sprains [10] or joint/ligamentous injuries in total [6,7] than the present study, it is clear that injury prevention strategies which aim to reduce muscle and ligamentous injuries may be particularly beneficial for amateur players.…”
Section: Discussionsupporting
confidence: 92%
“…Our expertise regarding injury rates (IR) in male amateur soccer players remains limited [5][6][7][8][9][10] Injury displays a relatively high range, with values starting from 2.72 injuries [10] of total exposure and reaching 36.9 injuries per 1000 h [9]. These variable IR values indicate that incident rates may vary from study to study, probably due to methodological differences and the sample type examined.…”
Section: Introductionmentioning
confidence: 99%